ANALISIS PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN ( Studi Kasus Pada Politeknik Negeri Ambon) - ABDUL HARIS TAMALENE (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
This study discusses the impact of corporate culture on job performance in Ambon State Polytechnic. The purpose of this study is to analyze whether company culture significantly influences work motivation. In addition, to find out more deeply how the application of organizational culture applied in Ambon State Polytechnic can foster organizational commitment and organizational performance. This research is a research that uses a mixed method. The first is quantitative, which is done with 85 samples. To it, regression analysis is treated using an instrument called the SP SS program, which shows that corporate culture has a significant effect on employee performance. Qualitatively, organizational culture reflects how the style and way of an organization carrying out its operational activities. The results showed that the organizational culture implemented by the Ambon State Polytechnic was able to grow organizational commitment so that it directly improved employee performance.